2017
DOI: 10.1111/aeq.12215
|View full text |Cite
|
Sign up to set email alerts
|

Checks, Balances, and Resistance: The Impact of an Anti‐Immigrant Federal Administration on a School for Immigrant Teenagers

Abstract: The 2016 presidential election was dominated by anti-immigrant rhetoric where truths counted for less than bombast, obscuring the fact that the majority of refugees and immigrants are women and children. This article describes how teachers and students in a school for newly arrived immigrants are adapting to the reality of the new administration. [Immigrant education; schooling for social justice; sanctuary schools; English Language Learners]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Educators willing to adopt asset‐based narratives and culturally relevant programming can help make the successes of community‐based organisations happen in mainstream schools and classroom settings too. Miranda’s (2017) study of how a high school for immigrant teenagers taught US politics before and after the 2016 US presidential election discusses the trend of educators engaging in community and professional development opportunities to better understand the rights of undocumented immigrants and how to support their students to make them feel welcome. Describing the refusal of teachers to maintain neutral political stances as they seek to keep their students safe, Miranda (2017) writes: ‘As a result of the 2016 presidential election, schools and districts across the country are attempting to reassert to their immigrant students and families that they belong in their schools and communities’ (p. 378).…”
Section: Narratives and Belonging: How Educators Shape The Educational Experiences Of Immigrant And Refugee Youthmentioning
confidence: 99%
See 1 more Smart Citation
“…Educators willing to adopt asset‐based narratives and culturally relevant programming can help make the successes of community‐based organisations happen in mainstream schools and classroom settings too. Miranda’s (2017) study of how a high school for immigrant teenagers taught US politics before and after the 2016 US presidential election discusses the trend of educators engaging in community and professional development opportunities to better understand the rights of undocumented immigrants and how to support their students to make them feel welcome. Describing the refusal of teachers to maintain neutral political stances as they seek to keep their students safe, Miranda (2017) writes: ‘As a result of the 2016 presidential election, schools and districts across the country are attempting to reassert to their immigrant students and families that they belong in their schools and communities’ (p. 378).…”
Section: Narratives and Belonging: How Educators Shape The Educational Experiences Of Immigrant And Refugee Youthmentioning
confidence: 99%
“…While youth from marginalised communities experience positive social and academic outcomes from building relationships with educators who value their cultural and linguistic ways of knowing (Kinloch & San Pedro, 2014; Orellana, 2016; Moinolnolki & Han, 2017), youth will discursively negotiate belonging and counter dominant narratives with or without the support of educators. To highlight a few examples among many, youth are challenging dominant narratives by authoring their own refugee narratives (Ryu & Tuvila, 2018), contesting marginalisation by creating youth‐led affinity spaces (Shirazi, 2019) and engaging in social action to support undocumented peers (Miranda, 2017). Educators can support the youth by helping them make welcoming spaces for themselves and their peers, exploring and embracing the complexities of their identities and collaboratively learning about each other in mutually beneficial ways.…”
Section: Narratives and Belonging: How Educators Shape The Educational Experiences Of Immigrant And Refugee Youthmentioning
confidence: 99%
“…More recently, research on the Trump era’s anti-immigrant policies notes that schools with predominantly White students have become hostile environments for vulnerable groups (Rogers et al, 2017). Miranda (2017) highlights the decisions a school made to adapt to Trump’s election by shifting language and making students feel safe. Ee and Gándara (2020) surveyed educators at 46 districts across the United States and found that immigration enforcement affects both immigrant and nonimmigrant students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…. to make sense of teachers' observable instructional practices" (Milner, 2017, p. 9), I join ongoing conversations among scholars and practitioners about the texture of power in racially diverse classrooms (Fine et al, 1997;Rubin, 2003) and educational responses to contemporary political events (Costello, 2016;Miranda, 2017;O'Connor & Mangual Figueroa, 2017;Rogers et al, 2017). As I examine the nature of teaching and learning in a school that endeavors to sustain its racially and culturally diverse students academically, relationally, and politically, I complicate widely held but often underexamined assumptions about the benefits of diversity in the classroom.…”
Section: Executive Summarymentioning
confidence: 99%